Draft Genome Sequence of an Isolate of Nontypeable Haemophilus influenzae from an Acute Exacerbation of Chronic Obstructive Pulmonary Disease in Tasmania - KC, Rajendra (Microbiol Resour Announc, 2020)
Nontypeable Haemophilus influenzae (NTHi) is an important cause of human illness, including pneumonia and acute exacerbations of chronic obstructive pulmonary disease (COPD). We report here the draft genome of an isolate of NTHi collected from the sputum of a patient presenting with COPD in Tasmania, Australia.